Milton Friedman on bailouts - Rockoff, Hugh (Journal of Financial Stability, 2022)
This paper analyzes the evolution of Milton Friedman’s thinking about bailouts. It covers bailouts of commercial banks, shadow banks and other financial firms, manufacturing firms, governments, financial markets, and other cases where the term is commonly used. It is based on his academic writings and on the many interviews, op-eds, letters to the editor, and so on through which he communicated his views during and after his transition from professor to public intellectual.